Advancement of existing healthcare setting through tele-medicine: the challenges faced in India - B., Swarna Priya; Srinath, Kalepu; Jammalamadaka, Anagha; Hindodi, Anurita (International Journal Of Community Medicine And Public Health, 2020)
Telemedicine is the mixed structure of tele-communication technologies and quality health care making it feasible for general populace to obtain superlative healthcare. Starting from video chat for medical services in 2000 to e-Sanjeevani OPD 2020, Indian healthcare reform has come a long way in achieving sustainable healthcare in which, the setting up of the National Telemedicine Taskforce by the Health Ministry of India, in 2005, played a huge role for various projects like the ICMR-AROGYASREE, NeHA and VRCs. Despite the lack of awareness among common public on Tele-medicine, it has a lot of benefits on existing health care settings which makes it to thrive and progress within a decade. Health systems and polices have a critical role in determining the manner in which health services are delivered, utilized and affect health outcomes. This article in brief discusses on the changes and advancement of traditional healthcare system, realizing the pace of timeline in bringing Tele-medicine into practice. As, international telemedicine initiatives are attaining quality healthcare, this article also describes the challenges of telemedicine in Indian healthcare settings.